(m, λ)-Berezin Transform on the Weighted Bergman Spaces over the Polydisk. (29th September 2016) - Li, Ran; Lu, Yufeng
Abstract : We prove that every bounded linear operator on weighted Bergman space over the polydisk can be approximated by Toeplitz operators under some conditions. The main tool here is the so-called ( m, λ ) -Berezin transform. In particular, our results generalized the results of K. Nam and D. C. Zheng to the case of operators acting on A λ 2 ( D n ) .